Transvaginal mesh repair for pelvic organ prolapse. Issue 4 (26th February 2014) - Jiang, Guojing; Yan, Bin; Wang, Yu; Ma, Qingliang
Abstract Aim We compared outcomes for traditional vaginal surgery with uterosacral ligament suspension (USLS) versus transvaginal mesh repair of pelvic organ prolapse (POP). Methods We performed a retrospective chart review of pelvic organ prolapse cases that occurred between February 2007 and December 2011. Success rates for traditional vaginal repair plus USLS and transvaginal mesh repair were determined. Results As compared with traditional surgery (n = 81), using mesh (n = 90) for stage III or IV prolapse resulted in higher rates of successful treatment. However, mesh repair also resulted in increased intraoperative blood loss and postoperative adverse events, such as pain and dyspareunia. Conclusion Traditional vaginal repair plus USLS was an improvement on traditional surgery, resulting in a higher anatomical success rate. On the other hand, both intraoperative and postoperative complications in mesh repair could be reduced by protective factors such as the surgeon's experience.